(3GdHOjYs - (3CHh GdMSf fUQ Hf GdMSf GdeQZjGfjs
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHh GdMSf fUQ Hf GdMSf GdeQZjGfi QVi Gddg Yfg gPG cJGH CdaJg ai GdHOjY dHYV GdENhGf GdQGZHjf ai GdCOH hGdefGaSjf ajg s
(3BNQgG (B:s
(3Ci eG jLO ef jYPQg ajg bGd (B: (3GdHMJQi ZOjQi ajc ef dGL EPG eG TchJ GdMH MQbfi edGeG Ci ef jYPQfi ajc ef dGL gPg UaJg Je GdcJGH HMeO Gddg hefg hGdMeO ddg hUdhJg Ydi SjOfG eMeO hBdg hSdGeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3hgh cJGH ai GdfbO GdCOHi Ydi WQjbI GdeJbOejfs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(264/1) s
Keywords: (3GdHdGZIs